Revision of the Oxynoemacheilus angorae group with the description of two new species (Teleostei: Nemacheilidae) - Yoğurtçuoğlu, Baran; Kaya, Cüneyt; Freyhof, Jörg (Zootaxa, 2022)
The Oxynoemacheilus angorae species group is revised and 10 species are recognised, two of which are described herein as new. Oxynoemacheilus anatolicus, O. angorae, O. eregliensis, O. germencicus, O. isauricus, O. nasreddini, O. mediterraneus, and O. theophilii are endemic to west and Central Anatolia. Oxynoemacheilus cinicus and O. mesudae, both from Büyük Menderes River drainage, are synonyms of O. germencicus. As First Revisers, we give priority to Oxynoemacheilus germencicus over O. cinicus. Oxynoemacheilus atili described from Lake Beyşehir basin is a synonym of O. eregliensis. Oxynoemacheilus axylos, new species, from endorheic Lake Tuz basin (Cihanbeyli, Gölyazı, Melendiz, and Samsam) is distinguished by possessing an almost truncate caudal-fin, a stout caudal peduncle, and elevated dorsal and ventral adipose crests. The new species is also distinguished by a minimum K2P sequence divergence of 1.6% in the mtDNA-COI barcode region from O. eregliensis, its closest relative. Oxynoemacheilus eliasi, new species, from the Küçük Menderes and Gediz River drainages, is distinguished by having small, embedded scales on the belly, a narrow suborbital groove in male, an emarginate caudal fin, the caudal peduncle depth 1.3–1.5 times in its length, and the body depth decreasing between the dorsal and caudal-fin bases. The new species is also distinguished by a minimum K2P sequence divergence of 2.7% in the mtDNA-COI barcode region from O. theophilii, its closest relative.